Links between soil properties and steady‐state solute transport through cultivated topsoil at the field scale. Issue 2 (6th February 2013) - Koestel, J. K.; Norgaard, T.; Luong, N. M.; Vendelboe, A. L.; Moldrup, P.; Jarvis, N. J.; Lamandé, M.; Iversen, B. V.; Wollesen de Jonge, L.
Key Points: 64 of 65 undisturbed soil columns exhibited preferential transport The strength of preferential transport was correlated with the bulk density The dominant transport process was inferred to be transport through macropores Abstract : [1] It is known that solute transport through soil is heterogeneous at all spatial scales. However, little data are available to allow quantification of these heterogeneities at the field scale or larger. In this study, we investigated the spatial patterns of soil properties, hydrologic state variables, and tracer breakthrough curves (BTCs) at the field scale for the inert solute transport under a steady‐state irrigation rate which produced near‐saturated conditions. Sixty‐five undisturbed soil columns approximately 20 cm in height and diameter were sampled from the loamy topsoil of an agricultural field site in Silstrup (Denmark) at a sampling distance of approximately 15 m (with a few exceptions), covering an area of approximately 1 ha (60 m × 165 m). For 64 of the 65 investigated soil columns, we observed BTC shapes indicating a strong preferential transport. The strength of preferential transport was positively correlated with the bulk density and the degree of water saturation. The latter suggests that preferential macropore transport was the dominating transport process. Increased bulk densities were presumably related with a decrease in near‐saturated hydraulic conductivities and as a consequence to larger water saturation and the activation of larger macropores. Our study provides further evidence that it should be possible to estimate solute transport properties from soil properties such as soil texture or bulk density. We also demonstrated that estimation approaches established for the column scale have to be upscaled when applied to the field scale or larger.